Archives Management System in the General Bureau and Papua Province Governor's Office Protocol - Ohoiwutun, Yosephina; Ilham, Ilham (Formosa Journal of Applied Sciences, 2023)
Focused research discusses the Archives Management System in the General Bureau and Protocol of the Papua Province Governor's Office. The method used is a qualitative approach.To obtain data, this is done through: Observation, Interviews and Documentation. To analyze various phenomena in the field, the following steps are carried out: Information collection, data reduction, data presentation, and drawing final conclusions. The results of this study show that the planning carried out in archive management is only general in nature, the organizing carried out in archive management has not been carried out effectively, the actuating in archive management has not gone well, so in-depth planning needs to be carried out in accordance with archival procedures starting from the creation of archives, use of archives, maintenance of archives, up to destruction of archives.